Krisis Motivasi Belajar Bahasa Arab Sebagai Bahasa Agama: Sebuah Kajian Empiris di Perguruan Tinggi Umum - Nasikhah, Atik Dina; Saraya, Sitta (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
In general universities, in accordance with Law No. 12 of 2012 Article 35 paragraph 5, it is mandatory to include courses based on Law No. 12 of 2012 Article 35 paragraph 3, including Religion, Pancasila, Citizenship, and Indonesian. In the courses that have been determined based on the law, it is stated that Arabic is not included in the general compulsory courses that must be present in general universities. The problem is that general universities have general compulsory courses on Religion but there are no compulsory courses on Arabic, even though Arabic can be said to be a religious language. Based on this problem, this research needs to be done. The focus of this research is to discuss student motivation to learn Arabic and a descriptive explanation related to whether Arabic is a religious language. The research method used is a qualitative descriptive analytical research method. Data collection uses observation, interviews, and documentation. The analysis used in this study uses analysis according to Miles and Huberman. The results of this study indicate that the majority of students at public universities have very limited Arabic language proficiency. Another factor contributing to the motivational crisis in learning Arabic is the lack of regulations at public universities regarding the mandatory study of Arabic, which is a religious language. Arabic and religion are interconnected and complement each other. Learning Arabic makes us Muslims who can understand and implement Islamic teachings properly and correctly.